Garcinia atroviridis fruit extract modulates lipid accumulation in 3T3-L1 adipocyte cells - Hanisuhana Hamidon (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
Obesity is the accumulation of excess body fat to the extent it may have an adverse effect on health. It is undeniably a complex disease with risk factors combination of genetics, lifestyle, nutrition, increasing age, and lack of physical activity. Alarming increase of obesity prevalence since past few years brings the concern to explore effective therapy against obesity. The hydroxycitric acid, HCA, is a potential compound in weight management that possesses a high market demand. It was commonly reported to be originated from Garcinia cambogia. There is little attempt to study the potential of our locally available underexplored G. atroviridis on its HCA content. This also has opened the gap to study the extract lipid alteration potential the on 3T3-Ll cell culture model. This present study aims to quantify the amount of HCA available in the fruit extract as well as to investigate its lipid modulation properties in 3T3-Ll cell culture model. The fresh fruit was macerated using ethanol and freezedried. Then, the HCA was screened and quantified using FTIR and HPLC analysis, respectively. The extract was further tested in vitro for its lipid modulation potential. Firstly, the cell viability assay was conducted to assess the possible extract's cytotoxic effect on the cell line. Then, the cell was induced to differentiate using differentiation medium in the presence of the extract. Differentiated adipocytes were analysed qualitatively and quantitatively using Oil Red O stain. The treatment's effect on the adipogenesis-related proteins, PPARy and C/EBPa were also investigated by means of western blot. The lipid content in the differentiated adipocytes was also confirmed with leptin ELISA assay. Finally, the adipolysis assay was conducted to identify the extract's effect on the breakdown of lipid. From the FTIR spectroscopy, the presence of HCA in the extract was confirmed based on the significant functional groups of hydroxyl, carbonyl, and lactone. Later, the HPLC analysis quantified about 11.35 ± 0.55 % (w/w) of HCA in the extract with retention time at 0.9 minute, corresponding to the standard. The extract was no cytotoxic on the cell line since the treatment did not cause any 50 % reduction in the cell viability, hence concentrations of 10, 45, and 60 μg/mL were chosen for subsequent assays. In adipogenesis assay, it was observed that increased co-treatment concentration inhibited the formation of intracellular lipid. This was further confirmed with spectroscopic absorbance of Oil Red O stain and absorbance value measured shows reduction. Co-treatment at 60 μg/mL significantly (p < 0.05) inhibited the adipogenesis. From the western blot analysis, the treatment only affects the expression of C/EBPa protein significantly (p < 0.05). It was concluded that the treatment supressed adipogenesis by inhibiting the C /EB Pa expression. Meanwhile, the leptin assay finding was also in agreement with adipogenesis analysis since the leptin released was significantly reduced (p < 0.05) at increased treatment concentration. Finally, the extract enhanced the adipocytes breakdown (adipolysis) significantly (p < 0.05) at 10 and 45 μg/mL of extract. Taken together, the findings indicated that the fruit extract of G. atroviridis plays a role in alteration of lipid accumulation with the intervention of protein associated with adipogenesis and enhancing the adipolysis. Understanding adipogenesis and its molecular mechanisms may provide clues for future strategies development in preventing and managing obesity. Hence, the G. atroviridis fruit can be proposed as one of weight management agents due to its lipid modulation properties.